JURIDICAL REVIEW OF CHILD MARRIAGE BASED ON LAW NUMBER 16 OF 2019 AMENDMENTS TO LAW NUMBER 1 OF 1974 CONCERNING MARRIAGE - Kartika, Nana (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this study is to determine the provisions for child marriage, the causes of child marriage, juridical analysis of child marriage regulated in Law Number 16 of 2019 Amendments to Law Number 1 of 1974 concerning Marriage. This type of research is a normative law, with a descriptive nature of research. The research methods used are literature research and qualitative research. The type of data used is Secondary Data. The validity of marriage meets the requirements of marriage, reaches the condition of marriage, namely the age limit in accordance with the provisions of Article 7 paragraph (1) of Law Number 16 of 2019 and is required that every marriage be recorded by state officials. Then a juridical analysis of the juridical analysis of from Law Number 16 of 2019 Amendments to Law Number 1 of 1974 concerning Marriage, by socializing the marriage law to children to prevent child marriage and explaining the consequences of underage marriage.